2013
DOI: 10.1111/1365-2656.12019
|View full text |Cite
|
Sign up to set email alerts
|

Same size – same niche? Foraging niche separation between sympatric juvenile Galapagos sea lions and adult Galapagos fur seals

Abstract: Summary 1.In vertebrates, patterns of resource utilization change throughout development according to age-and or size-specific abilities and requirements. Thus, interspecific competition affects different age classes differently. 2. Adults of sympatric species often show distinct foraging niche segregation, but juvenile resource use might overlap with adult competitors of similar body size. Resultant negative effects on juveniles can have important consequences for population dynamics, yet such interactions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 96 publications
(214 reference statements)
3
51
0
Order By: Relevance
“…2.1a).Device must be in line-of-sight range of base station(s) and/or mobile receiver(s) to record locations. Signal can be interrupted by terrain.[31, 32, 36, 37, 184]GPS Logger (Fig. 2.1a)Sirtrack F1GFastloc ® GPSArchivalMainly individuals with restricted ranges (e.g.…”
Section: Devices and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…2.1a).Device must be in line-of-sight range of base station(s) and/or mobile receiver(s) to record locations. Signal can be interrupted by terrain.[31, 32, 36, 37, 184]GPS Logger (Fig. 2.1a)Sirtrack F1GFastloc ® GPSArchivalMainly individuals with restricted ranges (e.g.…”
Section: Devices and Datamentioning
confidence: 99%
“…Study limited to specific timescales (e.g. pre-moult/breeding season).[36, 37, 185]Argos relay tags (Fig. 2.1c)SMRU 9000x SRDL; Wildlife Computers Mk10 SPLASH Tag; Sirtrack KiwiSat 101; Telonics ST-10 PTTArgosArgosVery widely used.…”
Section: Devices and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Published by Elsevier Ltd. All rights reserved. and interspecific interactions (Holmes, 1973;Sousa, 1994;Pulliam, 2000;Nicholls and Racey, 2006;Jeglinski et al, 2013). However, within-host symbiont distributions, and the way these vary in relation to host characteristics, changes in species' abundance, or symbiont co-occurrence among individual hosts, are poorly known for most host-symbiont systems (Choe and Kim, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the significant negative correlation between the time yearlings spent diving while at sea and their trophic position (d 15 N values) relative to their mothers (Fig. 3) indicates that yearlings obtain food when actively diving at sea (see also Jeglinski et al, 2012;Jeglinski, Goetz, Werner, Costa, & Trillmich, 2013). Using stable isotope analyses, Jeglinski et al (2012) showed that yearlings feed at a lower trophic level than pups, indicating that they are no longer entirely dependent on maternal input (which leads to the highest enrichment of d 15 N in skin tissue).…”
Section: Differential Dive Effort By Sons and Daughtersmentioning
confidence: 99%